State-owned Banks in the Transition : Origins, Evolution, and Policy Responses - Sherif, Khaled; Borish, Michael; Gross, Alexandra (Washington, DC: World Bank, 2013)
Many of the distortions in poorly performing economies do not originate in the banking sector, but where state banks still control a large share of the resources in the banking system, they continue to pose a risk to macroeconomic and fiscal stability. State banks are typically vehicles for patronage that worsen the prospects for competitive market development. Alternatively, these state banks can be ineffective shells that fail to perform a useful intermediation role once the government imposes effective hard budget constraints and a modern supervisory system. The most problematic state banks have been agricultural and industrial banks, whose original role was to finance state farms and industrial enterprises that employed large numbers of people and served as the backbone of the socialist economic mode. Banks now show stronger growth in deposits and capital in many countries in Central and Eastern Europe and the Baltics, suggesting that these countries have put into place structures that have helped to restore confidence in banking systems among creditors, investors, and the public. Recommended strategies are that Governments need to design strategies to reduce state banking in order to help create a stable banking environment. Governments should take measures to improve the business environment as part of a broad overall strategy to strengthen the financial system and end state ownership of banks. Such measures include providing support to improve corporate governance, reform judicial systems, build registries of collateral, reinforce creditors' rights and contract enforcement, modernize accounting and auditing practices, reduce administrative obstacles to business registration, and modernize bankruptcy laws.